2020
DOI: 10.1093/ecco-jcc/jjaa103
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the PIBD-classes Criteria: A Multicentre Validation

Abstract: Introduction The PIBD-classes criteria were developed to standardise the classification of children with inflammatory bowel disease [IBD], from Crohn’s disease [CD], through IBD-unclassified [IBD-U], to typical ulcerative colitis [UC]. We aimed to further validate the criteria and to explore possible modifications. Methods This was a multicentre retrospective cohort study of children diagnosed with IBD with at least 1 year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Finally, the diagnosis of L2 CD was based on physician's assessment, and it is possible that some patients that were identified as having isolated colonic CD in fact exhibit ileo‐colonic CD, atypical UC or IBD‐U. We were unable to follow the PIBD classes criteria developed by Birimberg‐Schwartz et al (31) (and its modified version by Ledder et al (32)) in order to accurately classify paediatric patients into different IBD phenotype (including colonic CD vs UC vs atypical UC vs IBD‐U). These criteria are based on 19 items divided into three tiers, and require detailed phenotyping of each patient, including clinical, endoscopic, histologic and imaging data.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the diagnosis of L2 CD was based on physician's assessment, and it is possible that some patients that were identified as having isolated colonic CD in fact exhibit ileo‐colonic CD, atypical UC or IBD‐U. We were unable to follow the PIBD classes criteria developed by Birimberg‐Schwartz et al (31) (and its modified version by Ledder et al (32)) in order to accurately classify paediatric patients into different IBD phenotype (including colonic CD vs UC vs atypical UC vs IBD‐U). These criteria are based on 19 items divided into three tiers, and require detailed phenotyping of each patient, including clinical, endoscopic, histologic and imaging data.…”
Section: Discussionmentioning
confidence: 99%
“…A recently genetic association study and systematic review of the epidemiology, serology, and microbiology of IBD has shown that isolated colonic CD could be an intermediate between ileal CD and UC [ 21 22 ]. The Pediatric IBD Porto group have developed new criteria, the “PIBD-Classes,” to differentiate pediatric IBD into five categories to standardize the classification of subtypes—typical UC, atypical UC, IBDU, colonic CD, and CD [ 23 24 25 ]. Evaluation of the entire gastrointestinal tract has become more important, and recent advances in imaging studies and endoscopic devices can help clinicians in examining the small intestine [ 26 27 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, some of these IBDunclassified cases later develop into either CD or UC. 13 In a small proportion of children, IBD (especially UC) coexists with primary sclerosing cholangitis (PSC-IBD). The distribution of inflammation in the lower GI tract is so typical that PSC-IBD is often considered as a separate phenotype, with relatively mild intestinal symptoms, most active inflammation in the proximal colon, rectal sparing, and backwash ileitis.…”
Section: Pediatric Inflammatory Bowel Diseasementioning
confidence: 99%